Geology of the Minami-Yamato Nunataks, East Antarctica - Katsushima, Takayoshi (1984)
P(論文) The Minami-Yamato Nunataks are situated at 71.9°-72.1°S latitude and 35.1°-35.3°E longitude, 40km southwest of the Yamato Mountains. The basement rocks exposed in this area are classified as follows : (1) Granitic gneiss, (2) Hornblende-biotite gneiss, (3) Clinopyroxene-biotite gneiss, (4) Basic dikes, (5) Acidic dikes. The gneissic rocks subjected to amphibolite facies metamorphism were intruded by various dike rocks, which are subdivided into basic dike I, acidic dikes, basic dike II in order of their emplacement. Basic dike rocks were also metamorphosed. On the basis of their modes of occurrences and petrographic features it can be concluded that the rocks composing the Minami-Yamato Nunataks are correlated with those of Massifs B and C in the Yamato Mountains. departmental bulletin paper